Black Phosphorus Quantum Dots Modified CdS Nanowires with Efficient Charge Separation for Enhanced Photocatalytic H2 Evolution. Issue 5 (20th January 2021) - Liu, Fulai; Wang, Zhuan; Weng, Yuxiang; Shi, Rui; Ma, Wangjing; Chen, Yong
Abstract: Constructing a high‐quality interface with strong coupling interaction is highly desirable in composite photocatalysts for the efficient interfacial charge transfer. Herein, we prepared black phosphorus quantum dots/CdS (BPQDs/CdS) binary composites with tight interfacial contact via a facile electrostatic self‐assembly approach for efficient photocatalytic H2 evolution. The optimized H2 evolution rate of 3 wt % BPQDs/CdS can reach up to 9.9 mmol g −1 h −1 in lactic acid aqueous solution, 99 and 5.5 times greater than that of pristine BPQDs and CdS, respectively. Benefiting from the strong interface interaction between CdS and BPQDs in well‐contacted BPQDs/CdS composites, efficient charge separation can be achieved, leading to enhanced photocatalytic H2 evolution activity. Notably, the rapid transfer of photogenerated electrons from CdS to BPQDs was unambiguously confirmed by time‐resolved transient absorption spectroscopy. Abstract : Photocatalysis : A 0D‐1D BPQDs/CdS composite with high‐quality interface was prepared by a facile electrostatic self‐assembly approach. The optimized H2 evolution rate of 3 wt % BPQDs/CdS can reach up to 9.9 mmol g −1 h −1 . The enhanced activity is attributed to the rapid transfer of photogenerated electrons from CdS to BPQDs, which is thoroughly demonstrated by time‐resolved TAS spectra.